Impact of conservation pits on growth and yield of mature rubber - George S; John J; Joseph P; Philip A; Punnoose K I (Journal of Rubber Research, 2007)
Runoff and erosion substantially and seriously limit crop production in a tropical country like India. Appropriate runoff management techniques that enhance water conservation and reduce erosion to acceptable rates minimise these effects. The effect of conservation pits on soil moisture conservation and growth and yield of rubber was evaluated in a field experiment conducted from 1998 to 2005 in a mature rubber plantation in the central region of the traditional rubber growing tract in India. The treatments comprised conservation pits taken at the rate of 100, 150, 200 and 250 ha-1 and a control without pits. The experimental field was well drained with an average gradient of 17;-22;. Growth and yield of rubber were significantly influenced by the presence of pits. Yield of rubber was enahnced by 15;in the plots with 250 pits ha-1. Soil moisture storage estimated at depths of 10, 20, 30, 40, 60 and 100 cm, was substantially higher where pits were at the rate of 250 ha-1, indicating the contribution of pits towards ground water recharge. The presence of pits positively influenced the leaf water potential. The quantity of soil conserved in the pits ranged from 4.58 t ha-1 as the number of pits increased from 100 to 250. The quantity of nutrient conserved ranegd from 12-29, 6-13 and 27-62 kg ha-1 of N, P an K respectively. The proposed field water harvesting technique was proved to be quite useful in the conservation of soil and water in rubber.
Keywords: Growth; Moisture; Nutrients; Runoff; Soil erosion; Water conservation; Yield